Interruption of bronchial circulation leads to a severe decrease in peribronchial oxygen tension in standard lung transplantation technique1 - Herold, Ulf; Jakob, Heinz; Kamler, Markus; Thiele, Rudolf; Tochtermann, Ursula; Seeburger, Joerg; Motsch, Johann; Gebhard, Martha-Maria; Hagl, Siegfried (European journal of cardio-thoracic surgery, 1998)
Objective: In clinical practice lung transplantation is the only procedure where the transplanted organ is left without its own arterial perfusion. With the interruption of the bronchial arteries the nutritive support is dependent on collateral flow by the pulmonary artery and the oxygen tension of desaturated central venous blood, representing an abnormal physiology. Methods: To analyze this problem systematically, we used a standard single left lung transplantation model in the pig (n=12). In accordance with the clinical standard, lung preservation was performed with modified Euro-Collins solution with addition of prostacycline. The duration of ischemia was set to 4 h. Before and after single left lung transplantation tissue oxygen tension in the peribronchial tissue was measured with Licox® tissue pO2 microprobes. For validation, the myocardial tissue oxygen tension was recorded simultaneously. The hemodynamic assessment included continuous flow measurement of the left and right pulmonary artery using Transsonic ultrasound flow probes. After transplantation the animals were observed for 4 h. For hypothetic augmentation of collateral blood flow to the peribronchial tissue we administered Nitric oxide (10 ppm) to the ventilation in six pigs (group B). Six pigs (group A) served as a control without the addition of nitric oxide (NO). All pigs were ventilated with a FiO2 of 0.5 resulting in paO2 values between 160 and 200 mmHg. Results: In both groups single lung transplantation led to a significant decrease in peribronchial tissue oxygen tension throughout the observation period. Pre-Tx values of peribronchial tissue oxygen tension (38.31±6.56 mmHg) decreased to 9.72±2.55 mmHg in group A and 10.3±3.61 mmHg in group B after 4 h, which could not be altered by a FiO2 of 1.0 (P≪0.0001). The addition of NO in group B led to a significantly augmented flow in the left pulmonary artery (0.63±0.31 l/min in group B vs. 0.46±0.26 l/min group A, P≪0.001) representing 67 vs. 49% of the pre-Tx flow in groups B and A, respectively, but the peribronchial tissue oxygen tension was not influenced (P>0.05). In both groups A and B, the central venous pO2 did not differ in the postoperative period (41.83±3.27 mmHg group A vs. 43.26±2.98 mmHg group B) and was kept in a comparable range to the pretransplantation values (45.23±3.41 mmHg pre-Tx). Conclusions: The persistence of a very low peribronchial tissue oxygen tension in the early phase after lung transplantation cannot be influenced by improved pulmonary artery flow and solely relates to the central venous pO2, which cannot be augmented by the addition of NO. This mechanism might be a trigger for anastomotic healing problems, infectious complications and later development of obliterative bronchiolitis (OB).
Gesehen am 12.03.2025